2009
DOI: 10.1007/s00606-009-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

The systematic value of nuclear genome size for “all” species of Tulipa L. (Liliaceae)

Abstract: Nuclear genome size, as measured by flow cytometry with propidium iodide, was used to investigate the relationships within the genus Tulipa L. (Liliaceae). More than 400 accessions representing 123 taxa from mainly wild-collected plants were investigated. Most species of Tulipa have the same basic chromosome number, 2n = 2x = 24. However, the somatic DNA 2C value (2C) is shown to range from 32 to 69 pg for the diploids. The largest genome contains roughly 3.4 9 10 10 more base pairs than the smallest and has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
134
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 29 publications
(46 reference statements)
4
134
1
1
Order By: Relevance
“…Primitive angiosperms are now supposed to have had small genomes; increases up to a factor of 1,000 have occurred independently in various modern taxa (Leitch et al 1998). Flow cytometry was successfully used to measure the 2C-value for the genera Hosta Tratt., Helleborus L., Clivia Lindl., Nerine Herb., Agapanthus L'Hér., Galanthus L., Narcissus L., Gasteria Duval., Tulipa L., etc., by Zonneveld ( , 2008Zonneveld ( , 2009), Zonneveld and Van Iren (2001), Duncan (2003, 2006), Zonneveld and Van Jaarsveld (2005) and . In this paper it is shown that genome size alone is not sufficient to discriminate all species of Eucomis.…”
Section: Introductionmentioning
confidence: 99%
“…Primitive angiosperms are now supposed to have had small genomes; increases up to a factor of 1,000 have occurred independently in various modern taxa (Leitch et al 1998). Flow cytometry was successfully used to measure the 2C-value for the genera Hosta Tratt., Helleborus L., Clivia Lindl., Nerine Herb., Agapanthus L'Hér., Galanthus L., Narcissus L., Gasteria Duval., Tulipa L., etc., by Zonneveld ( , 2008Zonneveld ( , 2009), Zonneveld and Van Iren (2001), Duncan (2003, 2006), Zonneveld and Van Jaarsveld (2005) and . In this paper it is shown that genome size alone is not sufficient to discriminate all species of Eucomis.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Tulipa L. (Liliaceae) has at least 87 species (Zonneveld 2009). These are divided in four subgenera, Tulipa, Clusianae (Baker) Zonn., Eriostemones (Boiss.)…”
Section: Introductionmentioning
confidence: 99%
“…These are divided in four subgenera, Tulipa, Clusianae (Baker) Zonn., Eriostemones (Boiss.) van Raamsd., and Orithyia (D. Don) Baker, and twelve sections (Zonneveld 2009). Genome size and the presence of nearly complete crossing barriers between the sections (Van Raamsdonk 1992;Van Raamsdonk and De Vries 1995) confirmed the close relationships of the species within the different sections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations